Inovasi Pendidikan Karakter “ASIK” (Aku Selalu Introspeksi Karakter) di SD Negeri Danasri Kidul 01 Kecamatan Nusawungu Kabupaten Cilacap - Sulistyawati, Ika; Fajar, Wildan Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of the ASIK (Aku Selalu Introspeksi Karakter) program as an innovation to strengthen character education in third-grade students of SD Negeri Danasri Kidul 01. The study used a descriptive approach with data collection techniques through observation and documentation. Data were analyzed using comparative descriptive analysis by comparing the condition of students' character before and after the program implementation, then strengthened through documentation analysis of learning activities. The ASIK program was implemented through four main activities, namely the Circle of Feelings, Dilemma Stories, Reflection Notes, and Heart Vitamins, which were designed to develop empathy, self-reflection, honesty, and responsibility. The results showed an increase in all character indicators, namely empathy from 54% to 85%, reflective from 54% to 77%, honesty from 46% to 69%, and responsibility from 54% to 85% after two weeks of implementation. These findings indicate that the ASIK program is effective as a habituation strategy that encourages the internalization of character values ​​through self-reflection, emotional involvement, and structured social interaction. This study provides a practical contribution in the form of a simple model that can be adapted by elementary schools to strengthen character education systematically and sustainably.